Joint replacement technology - Revell, Peter A. (Peter Allen), 1943- (Woodhead Publishing in materials., 2008)
Joint replacement has been one of the major successes of modern medicine. Its continued success depends on effective collaboration between clinicians and researchers across many different areas in science and medicine. This important book brings together the wide range of research in this area and its implications for clinical practice. The book sets the scene with introductory chapters on joint biomechanics and tribology, materials for joint replacement and their interactions with the body, and regulatory issues. Part two reviews the use of metals and ceramics as joint replacement materials, joint design, bone cements and cementless fixation techniques, failure mechanisms and ways of predicting the lifetime of replacement joints. The third part of the book summarises research on how prosthetic joints interact with the body, including biological causes of joint failure, sterilisation techniques and the use of drug delivery systems to enhance joint replacement. The final group of chapters reviews key issues in replacing particular joints including the hip, knee, ankle, shoulder and elbow as well as developments in intervertebral disc and tempero-mandibular joint replacement technology. With its distinguished editor and international team of contributors, Joint replacement technology is a standard reference for the engineering and materials scientific communities, as well as surgeons seeking the best treatment for their patients. Reviews joint biomechanics and tribologyConsiders the use of metals and ceramics as joint replacement materials, joint design and bone cementsSummarises research on prosthetic interaction with the body.